Challenges and Opportunities of Big data in Health Care: Afrozah Nadeem - Afrozah Nadeem, Afrozah Nadeem; SUNDUS MUNIR, SUNDUS MUNIR; Syeda Binish Zahra, Syeda Binish Zahra; sadia kousar, sadia kousar (International Journal for Electronic Crime Investigation, 2020)
The term big data is referring to huge amount of structured and unstructured data. The concept of bigdata is based on three V’s that are volume velocity and verity. Health care industry is produced hugeamount of data every day. As all the things and industries become globalized, the health care industryalso becomes digitalized. For the purpose to solve the human being health issue the researchapplies big data technique to analysis the huge amount of data. In this article complete review aboutusing of big data health care industry is presented. The main purpose of this article is to discussabout all the challenges which create hurdle to create opportunities in implementation of big data